PEER ASSESSMENT IN ADULT EDUCATION: CHALLENGES AND OPPORTUNITIES - Jurāne-Brēmane, Anžela (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Adult education as a part of lifelong learning requires the use of modern teaching methods. Peer assessment is topical as it promotes the involvement of participants in the learning process more actively. The research aim is to explore challenges and opportunities of peer assessment in adult education. Structured interviews were used to achieve the aim of the research and to answer the question: what are the challenges and opportunities of peer assessment mentioned by participants of adult continuing education course. Main research results are related to opportunities of experience sharing, better understanding of the topic, but challenges relies to refers to lack of the ability to comment and emotional aspects.